Phytoplankton biomass and size structure in Xiangshan Bay, China: Current state and historical comparison under accelerated eutrophication and warming. (May 2019) - Jiang, Zhibing; Du, Ping; Liu, Jingjing; Chen, Yue; Zhu, Yuanli; Shou, Lu; Zeng, Jiangning; Chen, Jianfang
Abstract: To explore the effects of coastal eutrophication and warming on phytoplankton biomass and cell size, we analyzed current and historical data for size-fractionated chlorophyll a (chla) in Xiangshan Bay, China. Results showed that micro- and nanophytoplankton overwhelmingly dominated (>84%) in all seasons. The contribution of micro-chla was significantly lower in warm than in cold seasons, whereas contribution of pico-chla showed the opposite result. Overall, the micro-chla contribution increased with decreasing pico-chla contribution from the stable, clear, eutrophic upper bay to the turbulent, turbid lower bay, indicating that phytoplankton size structure on a spatial scale was largely shaped by water column stability and light rather than by nutrients. Since the 1980s, phytoplankton biomass, primary productivity, and micro-chla contribution in Xiangshan Bay have increased sharply with increasing nutrient amounts and temperature. Additionally, it seems that algal bloom seasonality has shifted forward from spring to winter since the power plant operations in 2006. Graphical abstract: Unlabelled Image Highlights: Micro- and nano-sized fractions overwhelmingly dominated phytoplankton community. Large-celled phytoplankton tended to predominate in well-mixed water column. Microphytoplankton dominance has increased under eutrophication and warming. Phytoplankton biomass and primary productivity have increased sharply since the 1980s. Algal bloom seasonality has shifted forward because of thermal discharge.